1703. Hematologic Toxicity of Valganciclovir Prophylaxis in Solid Organ Transplant Recipients as a Function of Weight-adjusted Ganciclovir Exposure. (31st December 2020) - Campanella, Toni A; Roy, Amanda; Gintjee, Thomas J; Donnelley, Monica; MacDougall, Conan; Gallagher, Jason C
Abstract: Background: Valganciclovir (VGC), an oral prodrug of ganciclovir (GCV), is 60% bioavailable. Manufacturer-recommended doses are adjusted for creatinine clearance (CrCl), but not weight (wt), while GCV doses are adjusted for CrCl and wt. Patients exposed to excess GCV by not wt-adjusting VGC doses may be at risk of hematologic toxicity. The purpose of this study was to investigate the impact of body weight on VGC toxicity in solid organ transplant (SOT) recipients. Methods: This was a multicenter retrospective study at three academic medical centers of adult SOT recipients who received VGC for CMV prophylaxis between January 2016 and August 2019. The primary outcome was first occurrence of leukopenia within six months post-transplant. The primary predictor was the ratio between the patient's estimated GCV exposure based on the initial VGC dose prescribed and the equivalent prophylactic GCV dose accounting for the patient's CrCl and wt (rVGC:GCV). Results: The study included 231 patients, mostly lung (59%) and kidney (KT, 28%) transplants (Table 1). The rVGCV:GCV was 4.4 (range, 0.6-25.1, SD 4.5), and was significantly higher in KT (7.7 vs 3.0, p < 0.001). Leukopenia occurred in 133 patients (57.5%). After adjustment for type of transplant, rVGC:GCV ratio was not associated with increased odds (OR 0.97, 95% CI 0.91-1.04) or hazard of (HR 0.99, 95% CI 0.95-1.04) leukopenia. Exploratory analysis suggested threshold effects and interaction with transplant type: a rVGCV:VGC of > 3 was associated with time to leukopenia (HR 2.02, 95% CI 1.09-3.74) among non-KT patients but not KT patients (HR 0.99, 95% CI 0.56-1.76) (Figure 1). Table 1 Figure 1 Conclusion: Initial doses of VGC used for SOT CMV prophylaxis are estimated to result in significantly higher GCV exposures than IV GCV doses. A relationship with risk of leukopenia was only seen in non-KT patients, possibly because of rapid recovery of renal function and dose adjustment in KT patients. Disclosures: Jason C. Gallagher, PharmD, FIDP, FCCP, FIDSA, BCPS, Allergan (Consultant)Astellas (Consultant)Merck (Consultant, Grant/Research Support)Nabriva (Consultant)Qpex (Consultant)scPharmaceuticals (Consultant)Shionogi (Consultant)Spero (Consultant)Tetraphase (Consultant)